Professional crystal reports for Visual Studio.Net. - McAmis, David, ....- (Indianapolis : Wiley, 2003)
Crystal Reports is one of the world's leading software packages for creating feature-rich reports, and now it is fully integrated with Visual Studio .NET. With this book, you'll see how to produce elegant and effective reports for Windows and the Web.
Keywords: Programmeren